Monitoring honeybee (Apis mellifera) flight activity and within-day hive weight changes during rapeseed (Brassica napus) flowering - Atanasov, Atanas Z; Hristakov, Ivaylo S; Stoyanov, Kaloyan E; Zhelyazkov, Presiyan А (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Honeybee (Apis mellifera) flight activity and beehive changing weight during rapeseed (Brassica napus) flowering was evaluated. The research was carried out during the 2021 agricultural period in the northeastern region of Bulgaria, specifically in Yuper village. The experimental site is situated at 43°54'28.59" N, 26°23'49.02"E coordinates, with an elevation of 107 meters. Within the experiment, there were 130 bee colonies kept in Dadant-Blatt hives. The bees belong to the species known as (Apis mellifera macedonica). Throughout the research duration, the study focuses on tracking the quantity of bees leaving the hive (Nbee) and the changes in hive weight (Y) caused by the secretion of nectar during different time intervals throughout the day. The monitoring included external factors such as the temperature of the outside air (Tair), 0C, the humidity of the air (Hair) %,, and the surface temperature (Tsur) 0C, of the rapeseed inflorescences. The findings indicate a noteworthy and favorable relationship between Nbee and Y. The stronger correlation between Nbee, Y and Tsur was found. The other weather indicators as Tair and Hair are not correlated with Nbee and Y. The monitoring of the honeybee flight activity and beehive weight during rapeseed flowering will help the beekeepers to determine the suitable moment to expand the bee colonies in order to achieve optimal productivity.